Combining Defects in a Single Nanographene: A Fully Helical Saddle Ribbon - Cruz, Carlos M.; Castro-Fernández, Silvia; Maçôas, Ermelinda; Millán, Alba; Campaña, Araceli G. (Synlett, 2019)
The controlled preparation of well-defined distorted nanographenes by a bottom-up approach based on organic synthesis permits the direct establishment of unprecedented structure–property relationships in carbon nanostructures. The simultaneous incorporation of various defects in nanographenes affords highly curved structures with novel or enhanced photophysical properties. In this sense, we recently reported a fully helical and saddle-shaped nanographene ribbon containing the first undecabenzo[7]helicene unit. Both its linear and nonlinear optical properties are enhanced in comparison with those of other partially π-extended [7]helicenes. Moreover, the new superhelicene exhibits the highest emission dissymmetry factor (glum) reported to date for a homochiral nanographene. The combination of both nonlinear and chiroptical properties in nanographenes opens up new possible future applications for those distorted nanostructures.1 Introduction2 Synthesis of Embedded Seven-Membered Rings3 Combination of Defects: Seven-Membered Rings and π-Extended Helicenes4 Conclusions and Outlook
Keywords: nanographenes; helicenes; chirality; polycyclic aromatic hydrocarbons; optical properties; chiroptical properties